Web-Based Drug Inventory System with FIFO Method and SCM Approach at Risa Farma Pharmacy - Mayang Selpiyana; Anggun Fergina; Indra Yustiana (Komunitas Dosen Indonesia, 2025)
Drug inventory management plays a crucial role in pharmacy operations as it directly relates to drug availability, service accuracy, and the prevention of losses caused by expired medicines. However, many small-scale pharmacies still rely on manual recording, which is prone to stock discrepancies, delayed detection of near-expired drugs, and low administrative efficiency. To address these issues, this study developed a web-based drug inventory system implementing the First In First Out (FIFO) method combined with a Supply Chain Management (SCM) approach. The system was developed using the System Development Life Cycle (SDLC), which includes planning, requirements analysis, system design, implementation, and functional as well as user testing. The results demonstrate that the system successfully reduces potential stock recording errors by up to 75% compared to manual methods and improves transaction recording efficiency by an average of 40%. The SCM approach enables the system to automatically issue alerts when stock reaches a minimum threshold and to provide restock recommendations based on demand data. A User Acceptance Test (UAT) involving 10 respondents produced a satisfaction score of 86%, indicating that the system is effective, user-friendly, and beneficial for pharmacy operations. This study concludes that the integration of FIFO and SCM in a web-based drug inventory system improves data accuracy, enhances operational efficiency, and minimizes the risk of expired medicines. Nevertheless, the system still faces limitations related to data security, internet dependency, and its suitability primarily for small-scale pharmacies.